2013
DOI: 10.1093/mnras/stt241
|View full text |Cite
|
Sign up to set email alerts
|

Minimum variability time-scales of long and short GRBs

Abstract: We have investigated the time variations in the light curves from a sample of long and short Fermi/GBM Gamma ray bursts (GRBs) using an impartial wavelet analysis. The results indicate that in the source frame, that the variability time scales for long bursts differ from that for short bursts, that variabilities on the order of a few milliseconds are not uncommon, and that an intriguing relationship exists between the minimum variability time and the burst duration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 36 publications
6
81
1
Order By: Relevance
“…This finding is fully consistent with MacLachlan et al (2013), where it was also found (using a larger sample of short-duration GRBs) that the two histograms are quite broad and very similar in dispersion.…”
Section: Discussion and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is fully consistent with MacLachlan et al (2013), where it was also found (using a larger sample of short-duration GRBs) that the two histograms are quite broad and very similar in dispersion.…”
Section: Discussion and Resultssupporting
confidence: 91%
“…The ∆t min values in Figure 7 are bound from above by T 90 , and they do not strongly correlate with T 90 within the allowed region of the plot. Recently, MacLachlan et al (2013) have studied faint Fermi GBM GRBs and do find evidence for a correlation. We can reconcile our conclusions by identifying low SNR as the driving force in any apparent correlation.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…and Golkhou et al (2015) analyzed the MTS from the structurefunction method based on non-decimated Haar wavelets for a large sample of GRBs from Swif t and F ermi. They reported MTS values that are less dependent on the measurement noise level compared former works (e.g., Walker et al 2000;MacLachlan et al 2013;Sonbas et al 2014). Since this method get rid of artificial effect due top the noise floor, hereafter we adopt the MTS measurements reported in and Golkhou et al (2015).…”
Section: Samplementioning
confidence: 81%
“…The typical minimum variability timescale (MTS) for blazars is around one day (e.g., Vovk & Neronov 2013), where ultra-fast variability as short as 3-5 min at TeV energies is also found in some blazars (e.g., Aharonian et al 2007;Albert et al 2007;Aleksic et al 2014). The typical MTS of GRBs is around 0.5 s with the shortest timescale on the order of 10 ms (e.g., MacLachlan et al 2013;, where the MTS is much shorter than the overall duration (e.g., T90). The physical origin of the flux variation is unclear for both GRBs and blazars, where several models have been proposed to explain their temporal variability.…”
Section: Introductionmentioning
confidence: 99%
“…For short GRBs, the average dt is ≈10 −2 s (MacLachlan et al 2013). The detailed temporal structure of the gamma-ray lightcurve could not be determined by the GBM data for this weak event.…”
Section: Internal Shocksmentioning
confidence: 99%